1992
DOI: 10.1021/ja00033a018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thiol self-assembled films by laser desorption Fourier transform mass spectrometry

Abstract: havior is believed to be general for this class of intermediates.Acknowledgment. We are grateful to Kevin Peters and Erin O'Driscoll (University of Colorado) for their help in obtaining the picosecond spectra, to the University of Arkansas for a sabbatical leave, and to T. J. Meyer (University of North Carolina) for the use of his nanosecond equipment. We thank E. M. Arnett (Duke University) and R. A. McClelland (Toronto) for their thoughtful comments and suggestions. We appreciate the com-ments of a referee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
180
4

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(191 citation statements)
references
References 1 publication
7
180
4
Order By: Relevance
“…Previous results from ellipsometry and x-ray photoelectron spectroscopy have found preferential adsorption of longer chain alkanethiols from mixed thiol solutions. 22 Previous mass spectrometric studies using direct laser desorption 11,12 and TOFSIMS 7-10 demonstrated only the monomer species as the parent ion. The direct laser desorption results can be reconciled with our results in the following manner: low-energy electrons, that are formed by UV photoemission from the Au surface, are subsequently attached to the laser-desorbed dimer neutrals, leading to dissociation to form RS -monomer ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results from ellipsometry and x-ray photoelectron spectroscopy have found preferential adsorption of longer chain alkanethiols from mixed thiol solutions. 22 Previous mass spectrometric studies using direct laser desorption 11,12 and TOFSIMS 7-10 demonstrated only the monomer species as the parent ion. The direct laser desorption results can be reconciled with our results in the following manner: low-energy electrons, that are formed by UV photoemission from the Au surface, are subsequently attached to the laser-desorbed dimer neutrals, leading to dissociation to form RS -monomer ions.…”
Section: Resultsmentioning
confidence: 99%
“…Direct (single) laser desorption mass spectrometry has also been used to examine SAMs and has detected negative monomer ions. 11,12 In contrast, a recent thermal desorption mass spectrometry study of octadecanethiolate monolayers observed dimer ions (RSSR + ) using electron ionization of desorbed neutrals. …”
mentioning
confidence: 88%
“…Hemminger and coworkers first demonstrated that negative ions of SAMs can be formed by direct laser desorption. 44 Negative ions can only be formed with laser wavelengths shorter than 337 nm, indicating that the thermally desorbed neutrals are ionized by attachment of photoemitted electrons. 4 This mechanism of negative ion formation works well in the case of self-assembled monolayers, but is not a general method of analysis.…”
Section: Ion Formation During Single-laser Desorptionmentioning
confidence: 99%
“…Involvement of alkylthiolates (RS ± ) in Equation 1 is inferred by the formation of indistinguishable monolayers from the alkane thiols and dialkyl disulfides of the same hydrocarbon chains, [173] and substantiated by FTIR, [174] FTIR±mass spectrometry, [175] Raman spectroscopy, [176,177] XPS, [178±180] and electrochemical [181] measurements. However, no evidence has been obtained for the formation of molecular hydrogen.…”
Section: Self-assembled Monolayers (Sams)mentioning
confidence: 99%